Synergy Between MOOCs and Digital Competency Frameworks: A Case Study of the MOOC« Teach remotely » for Continuing Education in Morocco - Mounia LHAIBA; Ibrahim BELMIR (International Journal of Scientific Research and Innovative Studies, 2026)
This article examines the interaction between MOOCs for teacher continuing education and digital competency frameworks in Morocco. The objective is to understand how frameworks such as NUMEFA, UNESCO's ICT framework, and DigCompEdu influence the design and deployment of self-paced online courses. To achieve this, we conducted a case study of the MOOC «Teach remotely » offered on the « e-takwine» platform. An in-depth documentary analysis of its objectives, pedagogical content, and assessment methods was carried out to evaluate their alignment with framework requirements. The analysis reveals that while some aspects of the MOOC meet expectations, significant discrepancies exist in content structuring and assessment methods. These findings suggest areas for improvement, particularly a pedagogical reengineering approach to optimize content structuring and integrate assessments better suited for digital competencies. The proposed recommendations aim to provide Moroccan teachers with more effective and relevant continuing education programs aligned with national educational requirements. Keywords: MOOC, Competency Frameworks, Digital Skills, Continuing Education. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/614